BAFF blockade attenuates acute graft-versus-host disease directly via the dual regulation of T- and B-cell homeostasis - Jeon, Youngwoo; Lim, Jung-Yeon; Im, Keon-Il; Kim, Nayoun; Cho, Seok-Goo (Frontiers in Immunology, 2022)
B cell activating factor (BAFF) is associated with donor-specific antibodies and chronic graft-versus-host disease (GVHD) after allogeneic hematopoietic stem cell transplantation (allo-HSCT). However, the effects of BAFF on T cell physiological function have not been fully elucidated in acute GVHD. We examined the effects of belimumab, a monoclonal antibody targeting BAFF, for the treatment of acute GVHD. Therapeutic functional manipulation of endogenous BAFF can improve acute GVHD during the early posttransplant period. In this study, BAFF was shown to increase the proportions of CD4+IL-17+, CD4+IL-6+ Th17, and CD4+IFN-r+ Th1 cells, and to reduce the proportion of regulatory T (Treg) cells. Furthermore, the belimumab therapy group showed increased B220+IgD+IgM+ mature B cells, but decreased B220+IgD−IgM− memory B cells, B220+Fas+GL-7+ germinal center formation, and B220+IgD−CD138+ plasma cells. These results indicate that BAFF can alleviate acute GVHD by simultaneously regulating T and B cells. Interestingly, the BAFF level was higher in patients with acute GVHD after HSCT compared to patients receiving chemotherapy. This study suggests that BAFF blockade modulates activated T cell and B cell homeostasis in acute GVHD after allo-HSCT.